Human Affective (Emotion) behaviour analysis using speech signals: A review - M. N., Hasrul; M, Hariharan, Dr.; Sazali, Yaacob, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/